Reverse Logistics and the Circular Economy: A Study before and after the Implementation of the National Solid Waste Policy in Brazil - Aguirre Rodríguez, Elias Carlos [UNESP]; Hernández, Cecilia Toledo; Aguirre-Rodríguez, Elen Yanina [UNESP]; da Silva, Aneirson Francisco [UNESP]; Marins, Fernando Augusto Silva [UNESP] (MDPI, 2024)
This article analyzes Reverse Logistics (RL) practices associated with the concept of Circular Economy (CE), comparing studies conducted before and after the implementation of the National Solid Waste Policy (NSWP) in Brazil. Data from companies in the Sul Fluminense region were analyzed using the Analytic Hierarchy Process to prioritize RL practices and identify those related to CE. The research included companies from nine Brazilian economic sectors that engage in some form of RL. The comparison of results aimed to evaluate the influence of the NSWP on these practices, with data analyzed using the Super Decisions software (version 3.2) to establish priorities and aggregate them using the Aggregating Individual Priorities method. It was observed that the implementation of the NSWP in 2010 emphasized the importance of sustainability. Although the concept of CE is recent, its operationalization is based on consolidated RL practices such as recycling, remanufacturing, and material reuse. The study provides insights to optimize and expand these practices, facilitating the transition from a linear economy to a circular one.
Keywords: Circular Economy; National Solid Waste Policy; Reverse Logistics